2016
DOI: 10.1007/s11433-016-0332-1
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature heat transport of spin-gapped quantum magnets

Abstract: This article reviews low-temperature heat transport studies of spin-gapped quantum magnets in the last few decades. Quantum magnets with small spins and low dimensionality exhibit a variety of novel phenomena. Among them, some systems are characteristic of having quantum-mechanism spin gap in their magnetic excitation spectra, including spin-Peierls systems, S = 1 Haldane chains, S = 1/2 spin ladders, and spin dimmers. In some particular spin-gapped systems, the XY-type antiferromagnetic state induced by magne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 130 publications
(225 reference statements)
0
8
0
Order By: Relevance
“…35 The decrease with the addition of SPLA polymers is inevitable since PCL has lower modulus and tensile strength compared to PLA. 6,13,23,46 Zhao H and Zhao G also found a similar result and concluded that modulus decreased with the increase of blending ratio of PCL content. They observed the lowest values in the blending ratio of 30/70 in which the PCL content was maximum.…”
Section: Mechanical Propertiesmentioning
confidence: 64%
See 3 more Smart Citations
“…35 The decrease with the addition of SPLA polymers is inevitable since PCL has lower modulus and tensile strength compared to PLA. 6,13,23,46 Zhao H and Zhao G also found a similar result and concluded that modulus decreased with the increase of blending ratio of PCL content. They observed the lowest values in the blending ratio of 30/70 in which the PCL content was maximum.…”
Section: Mechanical Propertiesmentioning
confidence: 64%
“…PLA is known as a brittle biopolymer with high yield strength, modulus, and low elongation at break. 6,9,20,23,46 Since it is a very fragile material, it is generally used by adding plasticizers. Plasticizers are materials added to improve processability, flexibility and stretchability of the material and generally added to PLA in order to improve its toughness.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Intriguing heat conductivity results for one-dimensional spin systems with relatively small exchange interactions have been obtained for both organic and inorganic materials, see e.g. [32,[172][173][174][175] for S = 1/2 systems and [28,30,55,[176][177][178][179] for systems with large spin, see also the reviews [180,181].…”
Section: Discussionmentioning
confidence: 96%